Online and semi-online scheduling on two hierarchical machines with a common due date to maximize the total early work - Xiao, Man; Liu, Xiaoqiao; Li, Weidong; Chen, Xin; Sterna, Małgorzata; Blazewicz, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
In this study, we investigate several online and semi-online scheduling problems related to two hierarchical machines with a common due date to maximize the total early work.
Keywords: online and semi-online; early work; hierarchical scheduling; competitive ratio